14-3-3 proteins as potential therapeutic targets - Zhao, Jing (2011)
The 14-3-3 family of phosphoserine/phosphothreonine-binding proteins dynamically regulates the activity of client proteins in various signaling pathways that control diverse physiological and pathological processes. In response to environmental cues, 14-3-3 proteins orchestrate the highly regulated flow of signals through complex networks of molecular interactions to achieve well-controlled physiological outputs, such as cell proliferation or differentiation. Accumulating evidence now supports the concept that either an abnormal state of 14-3-3 protein expression, or dysregulation of 14-3-3/client protein interactions, contributes to the development of a large number of human diseases. In particular, clinical investigations in the field of oncology have demonstrated a correlation between upregulated 14-3-3 levels and poor survival of cancer patients. These studies highlight the rapid emergence of 14-3-3 proteins as a novel class of molecular target for potential therapeutic intervention. The current status of 14-3-3 modulator discovery is discussed.